2000
DOI: 10.1002/1097-4628(20001003)78:1<166::aid-app200>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poly(vinyl chloride)/chlorinated polyethylene blend composition on thermal stability

Abstract: Blends of poly(vinyl chloride) (PVC) with different ratios of chlorinated polyethylene (CPE) were degradated by the thermogravimetric method under dynamic conditions (50–600°C) in an inert atmosphere. The effect of the miscibility and composition of the PVC/CPE blends on the thermal stability were investigated. DSC curves of the blends show neither a shift of the PVC glass transition temperature nor a shift of the CPE melting temperature, which means that these blends are heterogeneous. The characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 18 publications
0
19
0
2
Order By: Relevance
“…The second and the third step occur in the temperature range of 369–444°C and 444–500°C, respectively. The former is corresponded to the degradation of AMS‐ABS and the latter is attributed to the elimination of low molecular weight hydrocarbons from the polyenes residue . In addition, as seen in the DTG curves, the temperature at the first peak is shifted to higher values combined with lower maximal rate of degradation (height of the peak) as the content of CPE increases.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The second and the third step occur in the temperature range of 369–444°C and 444–500°C, respectively. The former is corresponded to the degradation of AMS‐ABS and the latter is attributed to the elimination of low molecular weight hydrocarbons from the polyenes residue . In addition, as seen in the DTG curves, the temperature at the first peak is shifted to higher values combined with lower maximal rate of degradation (height of the peak) as the content of CPE increases.…”
Section: Resultsmentioning
confidence: 94%
“…These results are expected, since CPE exhibits a higher thermal stability than PVC. Similar to PVC, the dehydrochlorination is also the dominant reaction in the CPE degradation . However, PVC exhibits a fast zipper dehydrochlorination, while the dehydrochlorination of CPE is a slow elimination of random chlorine and occurs at a relatively higher temperature .…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogenated nitrile butadiene rubber (HNBR) and chlorinated polyethylene (CPE) are both special rubbers with many brilliant properties, e.g., aging resistance, thermal stability, oil resistance, and so on. They have excellent toughening effect in many polymer matrix, such as SAN, nylon, and PVC, etc. In our previous works, the toughening effect of CPE and HNBR in SAN/ASA blends has been studied, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Bao et al found that the HPAM removal efficiency of 36.3% was obtained within the 7 d period when HPAM served as a sole nitrogen source. [31][32][33][34] In this work, N-allyl-2-(2,4-dichlorophenoxy) acetamide (DCAP) as a functionalized hydrophobic monomer was copolymerized with sodium 3-(allyloxy)-2-hydroxypropane-1-sulfonate (APS), acrylamide (AM) and acrylic acid (AA). and Flavobacterium.…”
Section: Introductionmentioning
confidence: 99%